1957
DOI: 10.1002/aic.690030122
|View full text |Cite
|
Sign up to set email alerts
|

Void fractions in two‐phase steam‐water flow

Abstract: The pressure-drop characteristics associated with one liquid and one gaseous phase flowing concurrently in a pipe or tube have yet to be understood. The operation of evaporators, boilers, and condensers has long stimulated interest in the pressure drop of steamwater mixtures, and more recently this specialized case of one-component, two-phase flow has received even greater attention from the applications in cooling nuclear reactors. The two-phase-flow problems have not been amenable to thorough theoretical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1959
1959
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Isbin, Sher, and permit reliable prediction of holdup rotameter. After the manometer had Eddy (7) reported holdup data for and pressure drop in vertical upward reached a steady reading, the desired gas the steam-water system at essentially flow was metered with a second rotame- ter. 5.8 and 28.6 centipoises.…”
mentioning
confidence: 99%
“…Isbin, Sher, and permit reliable prediction of holdup rotameter. After the manometer had Eddy (7) reported holdup data for and pressure drop in vertical upward reached a steady reading, the desired gas the steam-water system at essentially flow was metered with a second rotame- ter. 5.8 and 28.6 centipoises.…”
mentioning
confidence: 99%
“…They also used the figure 8b. In a later [29] study, Isbin, et al , found that slight changes in the void fraction curves from the Martinelli values would improve the predictions of maximum mass flow rates considerably.…”
Section: C(ho)(th)mentioning
confidence: 96%
“…[13,18] [29] correlations and the results of entrainment experiments. The Isbin, et al , modified [42] momentum [29] ri9l c(HO)(TH) [75] by Isbin, et [44] and by pressure drop studies such as that of Mendler, et [41] dieted by the Martinelli-Nelson correlation, reaches the sonic velocity for the vapor phase. (20) is shown in figure 12.…”
Section: Predictions)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dukler et al (1964) showed that the Hughmark (1962) correlation for holdup is a good representation of the experimental data for these regimes. Isbin et al (1957) report pressure drop data for steam-water flows at atmospheric pressure in a 2.2-cm i.d. A correlation of the pressure drop from eq 8 with the data of Hughmark (1969) was found to be where N F r = ( g ) & 2 Table I11 shows the average absolute deviations between calculated and experimental total pressure drops for these data.…”
Section: Pressure Drop For Vertical Upward Flowmentioning
confidence: 99%